Analisis Proksimat Karbon Batang Jagung (Zea mays) di Kecamatan 2 x 11 Kayu Tanam sebagai Sumber Material Maju - Risya Yelfika; Umar Kalmar Nizar (Jurnal Periodic Jurusan Kimia UNP, 2023)
Carbon material is a material obtained from carbonized organic materials such as charcoal and biomass waste that is processed into carbon. Corn stalks contain cellulose, hemicellulose, and lignin which have the potential to be used as carbon sources for advanced materials. This study aims to analyze carbon from corn stalks. Corn stalks were carbonized with temperature variations of 250˚C, 300˚C, 350˚C, 400˚C, and 450˚C. The carbon of corn stalks formed was carried out by proximate analysis by testing the vapor content, ash content, and bound carbon. The results of the analysis show that the higher the carbonization temperature, the lower the vapor content and the bound carbon content, while the higher the ash content. In this study, the results of the carbon analysis of corn stalks in  Kecamatan 2 x 11 Kayu Tanam according to SNI 06-3730-1995 were samples at a carbonization temperature of 250˚C.